Mitochondrial Dynamics, ROS, and Cell Signaling: A Blended Overview - Valentina Brillo; Leonardo Chieregato; Luigi Leanza; Silvia Muccioli; Roberto Costa (Life, 2021)
Mitochondria are key intracellular organelles involved not only in the metabolic state of the cell, but also in several cellular functions, such as proliferation, Calcium signaling, and lipid trafficking. Indeed, these organelles are characterized by continuous events of fission and fusion which contribute to the dynamic plasticity of their network, also strongly influenced by mitochondrial contacts with other subcellular organelles. Nevertheless, mitochondria release a major amount of reactive oxygen species (ROS) inside eukaryotic cells, which are reported to mediate a plethora of both physiological and pathological cellular functions, such as growth and proliferation, regulation of autophagy, apoptosis, and metastasis. Therefore, targeting mitochondrial ROS could be a promising strategy to overcome and hinder the development of diseases such as cancer, where malignant cells, possessing a higher amount of ROS with respect to healthy ones, could be specifically targeted by therapeutic treatments. In this review, we collected the ultimate findings on the blended interplay among mitochondrial shaping, mitochondrial ROS, and several signaling pathways, in order to contribute to the dissection of intracellular molecular mechanisms involved in the pathophysiology of eukaryotic cells, possibly improving future therapeutic approaches.